Pleasantness shapes congruency effects in odor-induced taste enhancement - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

A sulfonate-rich gel electrolyte enables coupled polyiodide confinement and Zn2+ transport regulation for durable aqueous ZnI2 batteries - Qing Luo; Ling Wang; Simin Chai; Yuwei Li; Xin Lin; Jinpeng Guan; Zetao Chen; Caifeng Li; Na Li; Lin Zeng; Jianxiong Xu (Chemical Engineering Journal, 2026)

Coupled impact of air-conditioning anthropogenic heat and building cooling energy consumption in high-density old urban neighborhoods - Simin Yang; Yunfei Ding; Chengliang Fan; Wanling Lin; Dongyu Lian; Yundan Liao (Building and Environment, 2026)

Corrigendum to “Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties” [Food Res. Int. 214 (2025) 116601] - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

Polysaccharide-based ROS-responsive micro/nanomotors loaded with β-Carotene: Characterization, encapsulation, and enhanced antioxidant application - Fanghan Li; Linghui Li; Songyi Lin; Minghao Zeng; Hongyan Wang; Jiaxin Qiang; Yue Tang; Simin Zhang (Food Bioscience, 2026)

Combined toxicity of nanoplastics and microcystin-LR to sulfate-reducing bacteria and the underlying mechanisms - Wei Du; Hao Wu; Simin Wang; Lin Cao; Yanmei Feng; Xiang Wu (Environmental Pollution, 2026)

An intelligent decision support framework for generating flood control emergency plan using knowledge graph and fuzzy enhanced entity recognition model - Rengui Jiang; Lingzi Wang; Yongjiao Lin; Jiancang Xie; Yong Zhao; Jiaqi Zhai; Simin Wang; Xixi Lu (Environmental Modelling & Software, 2026)

Quercetin-loaded polysaccharide micro/nanomotors: enzyme-driven propulsion mechanism and targeted uric acid reduction performance - Zhiyu Yan; Hongyan Wang; Songyi Lin; Jiayi Qiao; Xiuping Dong; Fanghan Li; Xiaomeng Ren; Mingxian Zhang; Yifei Dong; Simin Zhang (Chemical Engineering Journal, 2026)

Effects of low-temperature vacuum frying on scallops quality and development of a machine learning-based quality prediction model - Haiyou Dong; Songyi Lin; Xiuping Dong; Bo Liu; Hongyan Wang; Simin Zhang (Food Control, 2026)

NeuroViOme: a viral orfeome collection for studies of neurodegenerative disease - Benjamin Weller; Chung-Wen Lin; Simin Rothballer; Michael A. Calderwood; Pascal Falter-Braun; Claudia Falter (Journal of NeuroVirology, 2026)
Neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease, Amyotrophic Lateral Sclerosis (ALS), and Multiple Sclerosis (MS) pose a global health challenge due to their progressive course and lack of curative therapies. These conditions lead to severe neurological decline, significantly impacting patient independence and quality of life, and ultimately result in lethal outcome. Emerging evidence suggests that viral infections contribute to the onset and progression of these neurological diseases, Leblanc and Vorberg (PLoS Pathog 18:e1010670, 2022), either by directly inducing neurological symptoms or by triggering immune responses resulting in neuropathology. Nevertheless, systematic studies of the direct interplay between viral and host proteins in neurodegeneration remain scarce. A key aspect of viral pathogenesis is direct interaction between viral and host proteins (protein–protein interactions, PPIs), which are essential for viral replication and can disrupt or redirect host cell function Kim et al. (Nat Biotechnol, 2022); Zhou et al. (Res Sq, 2022), potentially contributing to the development of diseases traditionally considered non-communicable. Understanding these molecular mechanisms is crucial for advancing diagnostic and therapeutic strategies in neurodegenerative conditions, particularly ALS and MS. To enable systematic studies of these interactions, we introduce NeuroViOme as ORFeome resource encompassing nearly all protein-coding sequences from nine viruses selected based on their prevalence, neurotropism, and mechanistic or epidemiological links to neurodegenerative processes. NeuroViOme includes ORFs from Enteroviruses (EV-A71, EV-D68, CVB3, Echovirus E30), Herpesviruses (HSV-1, EBV, HHV3/Varicella Zoster), the endogenous retrovirus HERV-K, and Polyomavirus JCPyV. To our knowledge, this represents the most comprehensive viral ORF set assembled for neurodegeneration research to date. The collection builds the foundation for interactome mapping and functional genomics analyses and provides a valuable basis for systematic studies of viral perturbations of host pathways.

Opportunities or challenges? Upgrading of periphery space with the rise of platform urbanism: Live streaming commerce in Yangtze River Delta, China - Lin Zou; Yiwen Zhu; Simin Yan (Applied Geography, 2026)

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

Highly effective masculinization of mandarin fish (Siniperca chuatsi) using Etonogestrel: A practical method for aquaculture and transcriptomic mechanism elucidation - Jiangwei Zhou; Simin Zhong; Shengyue Lin; Shuzheng Ye; Dingxian Chen; Chong Han; Qiang Li (Aquaculture, 2026)

Enhancing taste without salt or sugar: Cross-modal flavor modulation via olfactory cues - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Construction of a multilayer perceptron based intelligent platform for dynamic quality monitoring and shelf-life prediction of bivalves - Yi Yuan; Songyi Lin; Xiuping Dong; Bo Liu; Haiyou Dong; Jiaxin Qiang; Junbo Chu; Simin Zhang (Food Chemistry, 2026)

Application of physics-informed neural networks-based hybrid prediction models in campus thermal environment prediction - Yongbo Cui; Xiaoqing Zhou; Chengliang Fan; Haonan Lin; Simin Deng (Building and Environment, 2026)

Chitosan-based coatings and films: Mechanisms and applications in postharvest preservation of mangoes - Guohui Yi; Simin Fan; Huanqi Wu; Ajahar Khan; Ruchir Priyadarshi; Wanying Sun; Derong Lin; Yiqin Zhang (Food Packaging and Shelf Life, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

Quality enhancement of batter-coated oysters via low temperature vacuum frying technique and machine learning-based prediction models for shelf life and quality dynamics - Junbo Chu; Songyi Lin; Xiuping Dong; Bo Liu; Haiyou Dong; Simin Zhang (Food Chemistry, 2025)

Synthesis of magnetic zeolite from iron sludge and fly ash for simultaneous nitrogen and phosphorus removal - Huiping Zeng; Simin Li; Jiongru Liang; Zhanguo Li; Da Lin; Jie Zhang; Dong Li (Journal of Water Process Engineering, 2025)

Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2025)

Multi-asymmetry on residual sediment transport in the branching channels of the Yangtze Estuary - Simin Zhou; Chunyan Zhu; Jianliang Lin; Weiming Xie; Naiyu Zhang; Leicheng Guo; Qing He (Journal of Hydrology, 2025)

The interaction of atmospheric boundary layer and PM pollution in Mongolian Plateau: Implication for the threshold control strategy - Simin Yang; Yongjing Ma; Wenyu Zhang; Zhong Lin; Zhenguo Lu; Xingjun Zhou; Yuanzhe Ren; Xinbing Ren; Kecheng Peng; Yulong Tan; Yiming Wei; Masroor Ahmad; et al. (Atmospheric Research, 2025)

One-step construction of FeP/carbon aerogel composites and their efficient tetracycline removal mechanisms: Adsorption, in situ oxygen activation and electron transfer - Guilong Wang; Rongyuan Jiang; Juntao Chen; Simin Li; Guanfeng Lin; Beili Lu; Biao Huang; Jianwei Zhao; Lei Yang (Journal of Water Process Engineering, 2025)

Effects of dietary fiber on the quality of fried oysters and oil Permeation mechanism - Junbo Chu; Songyi Lin; Yuxin Xie; Lin Ma; Simin Zhang (Food Research International, 2025)

Effects of deep, air and vacuum frying on oyster quality and protein-mediated mechanism analysis via TMT quantitative proteomics - Junbo Chu; Songyi Lin; Baoshang Fu; Xiangning Meng; Jiaxin Qiang; Simin Zhang (Food Chemistry, 2024)

An Intelligent Indicator Film Based on Food Derived Materials for Real-Time Visual Monitoring of Salmon Freshness - Zhiyu Yan; Siqi Zhang; Songyi Lin; Ni Ding; Jiaxin Qiang; Tongtong Xie; Simin Zhang (Journal of Aquatic Food Product Technology, 2024)

Local defect structure design enhanced energy storage performance in lead-free antiferroelectric ceramics - Peixuan Li; Simin Wang; Jin Qian; Guanglong Ge; Luomeng Tang; Jinfeng Lin; Weiwei Yang; Jimin Lin; Weikang Lin; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2024)

Excellent low-E energy storage and fluorescence temperature sensing features in Bi0.5Na0.5TiO3-based transparent ceramics - Xiangfu Zeng; Xingan Jiang; Jinfeng Lin; Qifa Lin; Simin Wang; Yourong Wu; Xiao Wu; Min Gao; Chunlin Zhao; Tengfei Lin; Laihui Luo; Cong Lin (Chemical Engineering Journal, 2024)

Effect of tea extracts on heterocyclic aromatic amines and advanced glycation end products in roasting Eleutheronema Tetradactylum and lipid-mediated inhibition mechanism analysis - Ruichun Wang; Songyi Lin; Junbo Chu; Yi Yuan; Simin Zhang (Food Bioscience, 2024)

High-performance electrosorption of lanthanum ion by Mn3O4-loaded phosphorus-doped porous carbon electrodes via capacitive deionization - Guanfeng Lin; Guilong Wang; Yongzhi Xiong; Simin Li; Rongyuan Jiang; Beili Lu; Biao Huang; Haijiao Xie (Journal of Environmental Management, 2024)

Effects of quercetin and l-ascorbic acid on heterocyclic amines and advanced glycation end products production in roasted eel and lipid-mediated inhibition mechanism analysis - Junbo Chu; Songyi Lin; Yi Yuan; Siqi Zhang; Simin Zhang (Food Chemistry, 2024)

Enhancing acid stability of citral through internal structure modulation in nanostructured lipid carriers with solid lipids and phospholipids - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Research International, 2024)

Advancing real-time error correction of flood forecasting based on the hydrologic similarity theory and machine learning techniques - Peng Shi; Hongshi Wu; Simin Qu; Xiaoqiang Yang; Ziheng Lin; Song Ding; Wei Si (Environmental Research, 2024)

Obscuring effect of income inequality and moderating role of financial literacy in the relationship between digital finance and China's household carbon emissions - Simin Huang; Lin Yang; Chen Yang; Donghan Wang; Yiming Li (Journal of Environmental Management, 2024)

Encapsulation and release of citral using nanostructured lipid carriers: A study on the impact of different preparation methods - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Bioscience, 2023)

Altered functional brain networks in coronary heart disease: independent component analysis and graph theoretical analysis - Simin Lin; Puyeh Wu; Shaoyin Duan; Qianni Du; Shujia Guo; Zhishang Chen; Naiming Wu; Xiaoyan Chen; Ting Xie; Yi Han; Hengyu Zhao (Brain Structure and Function, 2023)

A multiple-methods approach to investigate dietary differences among nominally herbivorous fishes - Xianzhi Lin; Simin Hu; Yanyan Zhou; Hui Huang; Li Zhang; Sheng Liu (Marine Biology, 2023)

Selective and efficient removal of lanthanum ion in aqueous solution by P-doped porous carbon - Guanfeng Lin; Yongzhi Xiong; Guilong Wang; Simin Li; Rongyuan Jiang; Beili Lu; Yandan Chen; Biao Huang (Journal of Water Process Engineering, 2023)

Paper-assisted ratiometric fluorescent sensors for on-site sensing of sulfide based on the target-induced inner filter effect - Yao Lin; Simin Ye; Jinxiao Tian; Anqin Leng; Yurong Deng; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2023)

Impact of three phycospheric bacterial strains on the growth and fatty acid composition of Isochrysis galbana - Minnan Wu; Jiayi Cao; Yijun Xu; Simin Xu; Zhengbo Zhou; Mengmeng Shao; Ziyue Wang; Lin Zhang; Deshui Chen; Yuanyuan Wu; Jilin Xu; Xiaojun Yan (Algal Research, 2023)

Enhancing the Thermotolerance of Isochrysis zhangjiangensis Through Co-culturing With Algoriphagus marincola - Simin Xu; Jiayi Cao; Minnan Wu; Yijun Xu; Yuanyuan Wu; Kaixi Shang; Bin Ma; Lin Zhang; Deshui Chen; Xinyu Liu; Xiaojun Yan; Jilin Xu (Marine Biotechnology, 2023)

Vegetable extracts: Effective inhibitors of heterocyclic aromatic amines and advanced glycation end products in roasted Mackerel - Simin Zhang; Ruichun Wang; Junbo Chu; Chenyang Sun; Songyi Lin (Food Chemistry, 2023)

The potential mechanisms of skin wound healing mediated by tetrapeptides from sea cucumber - Zhihong Zheng; Na Sun; Zhiqiang Lu; Jingru Zheng; Simin Zhang; Songyi Lin (Food Bioscience, 2023)

Planar D-σ-A type thermally activated delayed fluorescence material with Intra- and intermolecular charge transfer characteristics - Simin Jiang; Jianyin Lin; Deli Li; Mengke Li; Yanmei He; Wentao Xie; Jiting Chen; Yiyang Gan; Guo-Xi Yang; Zhihai Yang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2023)

Streptomyces luteolifulvus sp. nov., a novel actinomycete isolated from soil in Nanjing, China - Shanshan Zhao; Ming Cheng; Congyu Lin; He Liu; Zhengran Wang; Kai Zhang; Simin Song; Qian Yang (Antonie van Leeuwenhoek, 2021)

Disturbance-Mediated Changes in Coral Reef Habitat Provoke a Positive Feeding Response in a Major Coral Reef Detritivore, Ctenochaetus striatus - Xianzhi Lin; Simin Hu; Yong Liu; Li Zhang; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2021)
Coral reefs are undergoing global phase shifts from coral-dominated to algae-dominated stages. The negative effects of this substratum shift on the diversity and abundance of fish have been well documented, but the influence on fish feeding is less studied, which may limit a deeper understanding of trophic pathways in such a disturbed system. In this study, we investigated the feeding response of a numerically dominant fish species Ctenochaetus striatus to different substrate types, including hard coral, short algal turfs (SATs, <5 mm), and long algal turfs (LATs, >5 mm), on reefs in the South China Sea. The biomass of C. striatus showed an inverted U-shaped relationship with coral coverage and a significant positive correlation with SAT coverage ( p < 0.05), indicating that rising SAT coverage associated with moderate coral loss provoked a feeding response in C. striatus . Stomach contents of C. striatus , analyzed using high-throughput sequencing (HTS), were dominated by algal sequences (relative read abundance, RRA > 80.0%), including macroalgae, filamentous algae, and microalgae (e.g., Symbiodinium and Prorocentrum ). The sequence number and diversity of microalgae (mainly dinoflagellates) tended to be abundant (RRA 13.5–36.5%) with increased SAT cover, but brown algae sequences (RRA 17.2–57.8%) or green algae sequences (RRA > 50.7% except one site) dominated the stomach content DNA in reefs with high coral cover and high LAT or macroalgal cover, respectively. Considering the limited ability of C. striatus to remove mature algae, macroalgal DNA might be from algal debris. Our results indicate that C. striatus populations respond positively to conditions of moderate coral loss through increases in body condition identified as increased biomass. These responses are correlated to the expansion of SAT’s as coral cover declined, however, this relationship reverses if coral loss is high due to the succession of LAT’s over SAT’s and a corresponding decrease in the quality of food available. Our use of HTS has nevertheless identified the importance of detritivory in the flow of energy through reefs in the Anthropocene which are increasingly becoming depauperate in hard coral.

Mechanisms of high-frequency dinoflagellate blooms of Scrippsiella trochoidea in Daya Bay, South China Sea - Yuan Tian; Simin Hu; Xianzhi Lin; Hui Huang; Xingyu Song; Yan Yan; Xuedong Xie; Tao Li; Sheng Liu (Journal of Oceanology and Limnology, 2021)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

A novel narnavirus from the plant-pathogenic fungus Magnaporthe oryzae - Yuan Lin; Jia Zhou; Xuan Zhou; Simin Shuai; Rendi Zhou; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2020)

Morphology and mechanics of chondroid cells from human adipose-derived Stem cells detected by atomic force microscopy - Simin Luo; Qiping Shi; Zhengang Zha; Ping Yao; Hongsheng Lin; Ning Liu; Hao Wu; Hua Jin; Jiye Cai (Molecular and Cellular Biochemistry, 2012)

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)